Linalool Exerts Dose Dependent Chemopreventive Effect Against 1 2 Dimethylhydrazine Induced Rat Colon Carcinogenesis - Nalini, Namasivayam (International Journal of Pharmaceutical & Biological Archive, 2014)
Linalool Exerts Dose Dependent Chemopreventive Effect Against 1 2 Dimethylhydrazine Induced Rat Colon Carcinogenesis